Archetypische Motive in erfolgreichen Werbespots: Eine hypothesenbasierte Forschungsperspektive auf das Konstrukt Markenpersönlichkeit - Sarah Engelhardt; Hans-Michael Ferdinand; Irene Kramer; Jens U. Pätzmann (Markenbrand, 2018)
– Which contribution can archetypal motives in commercials perform regarding a successful customer approach? Basing on the hypothesis that archetypes can contribute to the success of a brand personality, the relevance of archetypes for brand management is demonstrated. Then four successful commercials are analysed with a criteria catalogue concerning archetypal content. The success measurement of the commercials is based on international rankings, like the Festival de Cannes and the views of the respective spots on YouTube. The results show that the majority of the examined commercials have been conducted by use of archetypes.
Keywords: 650